SETTING UP A BUSINESS ENVIRONMENT TO INTRODUCE A NEW MATERIAL FOR PACKAGING IN INDONESIA - Andina Oktariani; Nyayu Lathifah Tirdasari; Nur Hasanah; Dikky Indrawan (Indonesian Journal of Business and Entrepreneurship (IJBE), 2020)
Along with the development of consumer behavior that focus on environment, it encourages company to use eco-friendly as attribute to the value preposition on generated product. Although Indonesian consumer aware of environment issues, still they prefer to choose another aspect instead of environmentally friendly on the product that bought by consumer. The aim of this research was to study the factors of environment business that able to support the success of new material development on the environmentally friendly packaging. The method that used in this research is factor analysis. The result of this research show that there are 2 (two) cluster of factors which supported the success of new material development on the environmentally friendly packaging, first factor is advocacy factor towards the innovation of using new material that competitive and logistic infrastructure factor of new material which supported by institutional network. The study is useful for policy maker to organize the right strategy formulation to be implemented on the development of new resource for the environmentally friendly packaging. Keywords: new material, packaging, eco-friendly, factor analysis